I Will Do It If I Enjoy It! The Moderating Effect of Seeking Sensory Pleasure When Exposed to Participatory CSR Campaigns - Ruiz de Maya, Salvador; Lardín-Zambudio, Rafaela; López-López, Inés (Frontiers in Psychology, 2016)
In an attempt to gain differentiation, companies are allocating resources to corporate social responsibility (CSR) initiatives. At the same time, they are giving consumers a more active role in the process of creating value. In this sense, consumer participation represents a new approach to gain competitive advantage. However, the effectiveness of consumer participation in CSR campaigns still remains unknown. With the purpose of shedding light on this issue, this paper shows that participatory CSR campaigns lead to greater consumer perceptions of CSR, which in turn results in more favorable attitudes toward the company. Furthermore, the effect is stronger for sensory pleasure seekers, whose involvement with the experience is greater. The findings contribute to the CSR literature and reveal important implications for marketers.